The great canon of st. Andrew of Crete. Scriptural, liturgical and hesychastic invitation for an encounter with God - Leśniewski, Krzysztof (Vox Patrum, 2018)
The Great Canon of St. Andrew of Crete is a masterpiece of Byzantine hymnography. Due to its liturgical use during the Great Lent in the Orthodox Church for more than a thousand years it has played a very important role in the process of spiritual preparing for the feast of the Resurrection of Christ. In the Orthodox consciousness the Great Canon is first of all the Lenten special invitation for personal repentance (and more specifically “a change of mind” – met£noia) and compunction (kat£nuxij). The whole content of the Great Canon, in the vast majority woven from biblical phrases and referring to the essential events of salvation history, has the purpose of reshaping a believer’s life according to the Divine Wisdom. This “ecclesial liturgical act” helps to release the faithful not only from the bondage of sin but also from evil thoughts (ponhroˆ logismo…) and destructive passions (p£qoi). Based on an analysis of issues and terminology of the Great Canon it seems to be a well-founded argument that it is a work that combines the Eastern Orthodox use of the Bible, and the hesychastic tradition in the liturgical context.